2009
DOI: 10.1177/0363546509349765
|View full text |Cite
|
Sign up to set email alerts
|

Patient Profiling in Cartilage Regeneration: Prognostic Factors Determining Success of Treatment for Cartilage Defects

Abstract: This study illustrates the influence of patient age and defect location and age on clinical outcome 3 years after treatment of a focal cartilage lesion in patients with a traumatic knee injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 25 publications
3
105
3
2
Order By: Relevance
“…20 Results after ACI showed a failure rate in older patients that is comparable to rates reported in younger patient groups. 12,21 Highlighting the patients age, de Windt et al 22 showed in a prospective study treating 55 patients with MFx and ACI that the KOOS (Knee injury and Osteoarthritis Outcome Score) improvement was significantly better for patients under 30 years compared with older patients. Data of a randomized controlled trial with 80 human subjects treated with ACI or MFx by Knutsen et al 23 are in accordance with findings from de Windt et al 22 Both groups of authors concluded that the patient age influences the clinical outcome of ACI as of MFx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Results after ACI showed a failure rate in older patients that is comparable to rates reported in younger patient groups. 12,21 Highlighting the patients age, de Windt et al 22 showed in a prospective study treating 55 patients with MFx and ACI that the KOOS (Knee injury and Osteoarthritis Outcome Score) improvement was significantly better for patients under 30 years compared with older patients. Data of a randomized controlled trial with 80 human subjects treated with ACI or MFx by Knutsen et al 23 are in accordance with findings from de Windt et al 22 Both groups of authors concluded that the patient age influences the clinical outcome of ACI as of MFx.…”
Section: Discussionmentioning
confidence: 99%
“…24 Concerning the ACI, an increased rate of hypertrophy was found for patellar defects, but no correlation was found for the occurrence of delamination, insufficient regeneration, and disturbed fusion. 25 de Windt et al 22 analyzed in a prospective cohort study the prognostic value of defect location (medial vs. lateral) on clinical outcome measures 3 years after cartilage therapy for a focal cartilage lesion in ACI and MFx. The authors found a significant better KOOS score for medial than for lateral lesions and therefore concluded that the defect location is related to clinical outcome of ACI and MFx.…”
Section: Discussionmentioning
confidence: 99%
“…1 Understanding this will have implications for the treatment of cartilage defects, 2 which in themselves predispose to osteoarthritis if left untreated. 3,4 Several treatment modalities for focal cartilage defects are based on the use of autologous tissue or cells from areas in the affected joint that are not exposed to mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of microfracture were independent of defect size in the study of de Windt et al 3 Thus, defect size may be a predictor of outcome for some treatments, but not others.…”
Section: Smentioning
confidence: 87%